2022
DOI: 10.21037/jhmhp-21-91
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dual degree, gender, and specialty on obtaining leadership positions in academic settings: a multi-institutional study

Abstract: Background: Disparities in advanced degrees, gender, and specialty for medical leadership in academia have not been described. Methods:In this cross-sectional multi-institutional study, the authors used the University of California (UC) employee database and organization charts to compile the physicians and medical leaders at 6 academic centers. Chi-square testing was used to identify factors associated with leadership positions.Results: Among physicians in leadership 34.6% had dual degrees compared to 25.3% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While we are working to determine the impact this may have on PCP alumni, studies have indicated that physicians with an MPH have higher rates of assuming leadership roles and conducting public health research. 32,33 When the PCP began through the support of an HRSA grant, some stakeholders were concerned about its sustainability in a private medical center with a large focus on research, specialty, and hospital-based training. Over time, sustainable leadership, programming, institutional funding support have allowed the PCP to thrive and become part of the university fabric.…”
Section: Discussionmentioning
confidence: 99%
“…While we are working to determine the impact this may have on PCP alumni, studies have indicated that physicians with an MPH have higher rates of assuming leadership roles and conducting public health research. 32,33 When the PCP began through the support of an HRSA grant, some stakeholders were concerned about its sustainability in a private medical center with a large focus on research, specialty, and hospital-based training. Over time, sustainable leadership, programming, institutional funding support have allowed the PCP to thrive and become part of the university fabric.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, most of them are not in the field of economics (i.e., MBA or MHA) but are PhD and MPH degrees. 26 Hence, less than 3% of hospital or health system CEOs hold MD and MHA/MBA dual degrees.…”
Section: Educational Backgrounds and Academic Degrees Of Current Heal...mentioning
confidence: 99%